Peran Lembaga Mediasi Dalam Perkara Perceraian Sebagai Upaya Memberikan Perlindungan Terhadap Perempuan Dan Anak - Ummu Salamah; Ismail Rumadan; Ciptro Handrianto; Alfurqan (Muwazah, 2022)
The focus of this study is to assess the role of divorce mediation institutions to protect women and children. In the case of divorce, the role of mediation institutions is urgently needed as an effort to protect women and children whose rights are often ignored which causes prolonged suffering. The issues raised in this study is the urgency of mediation in divorce cases and the role of mediation as an effort to provide protection for women and children. The method in this research is normative research, by examining the sources of data obtained through the literature as well as examining the results of mediation in the Religious Courts contained in the Peace Deed. The results of the study showed that mediation institutions have a significant role in resolving divorce cases. With the role of mediation and the expertise of a mediator, the conflicting members can reconcile in realizing a harmonious family. If it is not possible to reconcile, then the parties agree to fulfil the rights of the children to benefit the child as stated in the Peace Act.